E-Readiness Of Teachers To Integrate Ict In Teaching And Learning Post Covid 19 Pandemic: Case of Eswatini - Dludlu , Mzomba Nelson (Advances in Social Sciences Research Journal, 2020)
The current crisis in Eswatini brought by the Covid 19 pandemic calls for the education sector to move digital education from the peripheral role in leaning delivery to the center of the process of teaching and learning. Digital teaching and learning has become mainstream overnight. All schools were closed and the face-to-face teaching and learning approach was stopped indefinitely. This prompted new direction in research and innovations. The study was therefore conducted to take a snapshot on the E-readiness of Agriculture teachers to integrate ICT in their teaching post the Covid 19 pandemic. A survey research design employing the quantitative approach was conducted with all (N=284) agriculture teachers in Eswatini to (1) describe the E-readiness of Agriculture teachers to integrate ICT in their teaching and learning, (2) identify the support given to teachers towards ICT integration available in schools, and (3) to describe the teachers’ educational level and courses related to ICT integration in teaching. A valid and reliable instrument was designed with a Cronbach Alpha reliability coefficient of (r = .80) was used to collect data. Frequencies and percentages statistics were used to analyse data. Findings associated with teachers’ readiness to integrate ICT in their teaching were: (1) teachers had personal laptops and were using them to support teaching of agriculture, (2) teachers perceived themselves as digitally proficient in using ICT tools to facilitate teaching and learning, (3) teachers had free access to computers in schools, (4) more than half of the schools offering agriculture had internet connectivity, (5) ICT was offered as an examinable subject in the majority of schools, and that (5) teachers had taken basic computer course their pre-service teacher preparatory training. It is recommended that all teacher training institutions design and offer courses on instructional technology to equip all teachers in schools to use technology to enhance their teaching skills.